Comparison of the Effects of Impaired Fasting Glucose and Impaired Glucose Tolerance on Diabetic Development Risks on HbA1c Levels: A Retrospective Study - Aydın, Abdülkadir; Atadağ, Yıldız; Öksüz, Ahmet; Kaya, Didem; Aydın, Nagehan Esra (Journal of Surgery and Medicine, 2017)
Aim: The process between normal glucose metabolism and diabetes is called the prediabetic period. This period is impaired fasting glucose (IFG), impaired glucose tolerance (IGT) or glycosylated hemoglobin A1c (HbA1c) level of 5.7% -6.5%. IFG, IGT or IFG+IGT, shows increased risk of developing diabetes. The aim of this study is to compare the risk levels of diabetes development between glucose metabolism disorders. Methods: Patients who underwent oral glucose tolerance test (OGTT) and whose HbA1c values ​​were measured before and after the test on a quarterly basis and did not have diabetes in 2016, were scanned through the automation system and taken into study. Patients with HbA1c levels between 5.7 and 6.4% were evaluated as prediabetic and an increase in the HbA1c levels in these patients from 5.7% to 6.4% was considered to increase the risk of developing diabetes. Patients were divided into three groups according to the presence of isolated IFG, isolated IGT and IFG + IGT. Patients with IFG were group 1, patients with IGT were group 2, and patients with IFG + IGT were group 3. Correlation analysis was performed between the groups on HbA1c levels. Analyzes were performed using the SPSS 22.0 program. Mann Whitney U Test was used for descriptive statistical methods as well as for non-normal distribution of measured values. Significance was evaluated at p <0.05. Results: In the study period, 706 patients who had OGTT in our hospital and who had HbA1c levels before and after OGTT on a quarterly basis were determined. The number of patients in Group 1 was 272; in group 2 was 222 and in group 3 was 212. Compared to the HbaA1c levels of groups, the risk of diabetes development in Group 1 was statistically low compared to group 2 and 3 (p<0,001). No statistically significant differences were detected between group 2 and 3 (p=0,381). Conclusions: As a result of our study, patients with isolated IGT and IFG+IGT were found to be significantly higher than patients with an isolated IFG of diabetes development risks. There was no apparent difference between those with an isolated IGT and the IFG+IGT.